The Influence Of Total Quality Management On The Development - Boulahlib, Loutfi (جامعة الوادي University of Eloued, 2024)
Total Quality Management (TQM) and the development of intellectual capital go hand-in-hand in organizations. TQM enables continuous improvement and customer satisfaction, which are essential for success in a knowledge-driven economy. TQM intersects with knowledge management, creating, utilizing, and preserving intellectual capital. Examples of TQM success stories include Toyota, General Electric, Tesla. Intellectual capital fuels innovation, adaptability, and strategic decision-making, providing a sustainable competitive advantage. The challenges in implementing TQM for intellectual capital include resistance to change and resource constraints. However, there are strategies available to overcome these challenges and maximize knowledge assets. TQM plays a critical role in enhancing intellectual capital and offers recommendations for organizations seeking to optimize their knowledge assets.
Keywords: Total Quality Management (TQM); Intellectual Capital; Knowledge Assets; Knowledge Management.